PENGEMBANGAN SOFT SKILL BERBASIS KARIR PADA SMK DI KOTA SEMARANG - Utaminingsih, Sri (Fakultas Ekonomi, Universitas Negeri Semarang, 2011)
The objectives of the study was to find and develop the soft skilllearning model based careers on Vocational High School (SMK) with TourismCluster through a set of tryout and validation. The soft skill development basedcareers was expected to improve Vocational High Schools’ graduates and fulfillthe qualifications which were set by BI (Business and Industry). It was relevant to the President’s policy to improve Indonesian workers. The specific purposes ofthe study were: (1) to formulate the development of soft skill model design based careers on Vocational High School, (2) to find the soft skill development model based the effective careers on Vocational High Schools, (3) to compile the soft skill model guidance. This study used Research and Development approach, then continued to the field study process, developing the model design, tryout and finally, validation. At the introduction study, it was identified the values and soft skills supporting careers in business and industry. Then, those values became the foundation to (1) formulate the model design, and (2) compile the model develop the soft skills collaboratively involving the parties and stakeholders related to Vocational High Schools with Tourism Cluster, (3) create an effective modelguidance. From the process of development above, it was obtained the model design and the soft skill development model guidance to improve the graduates’ careers.